2020
DOI: 10.1016/j.breast.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based or home-based administration of oncology drugs? A micro-costing study comparing healthcare and societal costs of hospital-based and home-based subcutaneous administration of trastuzumab

Abstract: Objective: To investigate resource use and time investments of healthcare professionals, patients and their family and to compare healthcare and societal costs of one single hospital-based and one single home-based subcutaneous administration of trastuzumab in The Netherlands. Method: We conducted a bottom-up micro-costing study. Patients diagnosed with HER2þ early or metastatic breast cancer were recruited in four Dutch hospitals. For healthcare costs, data were collected on drug use, consumables, use of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…First, a lack of data on the number of at-home infusions and their associated costs meant that at-home administration was not implemented in our model. A Dutch study comparing at-home and in-hospital administration of trastuzumab showed that the costs are comparable overall for the two settings [ 51 ]. Although the healthcare-related costs of at-home administration were higher compared with in-hospital administration, societal costs were lower due to reduced patient travel costs and productivity losses.…”
Section: Discussionmentioning
confidence: 99%
“…First, a lack of data on the number of at-home infusions and their associated costs meant that at-home administration was not implemented in our model. A Dutch study comparing at-home and in-hospital administration of trastuzumab showed that the costs are comparable overall for the two settings [ 51 ]. Although the healthcare-related costs of at-home administration were higher compared with in-hospital administration, societal costs were lower due to reduced patient travel costs and productivity losses.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies are evaluating home chemotherapy as an alternative to hospitalization, especially for pediatric cancer patients. Studies focused on different outcomes, such as cost [ 84 , 85 ], adherence [ 86 ], safety [ 87 ], compliance, satisfaction, and quality of life [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, productivity losses for unpaid work on part of the patient and of their informal caregiver during the friction cost period ( 40 ) were included. Such losses were assumed to be linked to first- and second-line treatment administrations ( 46 ). The costs were based on hourly proxy costs for cleaning labor in the Netherlands ( 40 ).…”
Section: Methodsmentioning
confidence: 99%